Emergent Endovascular Repair of Challenging Aortocaval Fistula With Hostile Anatomy. (July 2017) - Wang, Yuewei; Yu, Wenjuan; Li, Yongxin; Wang, Haofu
Aortocaval fistula (ACF) is a rare complication. Endovascular repair is an option for this fatal condition. However, endoleak and persistent fistula may occur and lead to technical failure. We performed endovascular repair for 3 cases of challenging ACF with hostile anatomy. Patient 1 was an 80-year-old man who complained of abdominal distension and lower limb edema for 15 days. He had renal and cardiac dysfunction. Computed tomography angiography (CTA) showed an ACF and extreme tortuosity of right iliac artery. The super-stiff guidewire could not pass the right iliac artery. We performed endovascular repair and an occluder was used to block the right external iliac artery. Postoperative CTA showed migration of the occluder, and we ligated the right external iliac artery. The patient survived for 5 years. Patient 2 was a 78-year-old man who complained of an acute abdominal pain for 30 hours. Computed tomography angiography showed great neck angulation (63.3°) and a huge aneurysm (9.9 cm in diameter). A type 1A endoleak occurred and an aortic cuff was deployed at the proximal seal zone. Meanwhile, a type 3 endoleak occurred because of the migration and detachment of the left iliac limb. Another stent-graft was deployed to connect the iliac limb. The patient was followed up for 1 year and remained in a good condition. Patient 3 was a 74-year-old man who experienced severe abdominal pain for 1 day. Computed tomography angiography showed great neck angulation (66°) and a huge aneurysm (10.1 cm in diameter). A type 1A endoleak occurred, and an aortic cuff was deployed at the proximal seal zone. The patient was followed up for 6 months. In conclusion, ACF is a rare but a fatal condition. Acute cases and chronic cases with instable hemodynamics need urgent diagnosis and surgical intervention. Endovascular repair is an efficacious alternative to the traditional open repair.